"Boss ceiling effect": brand downgrading consumption of workplace employees. Issue 7 (12th December 2019) - Jia, Fang; Yang, Zhilin; Ji, Li; Xu, Shen
Abstract : Purpose: Previous literature suggests that people might purchase symbolic products to signal their social identity. However, in the organizational context, subordinates as customers might choose products with less brand prestige than what they want and can afford, just to make sure their choices are below the invisible "red-line" set by the brands of their supervisors. The authors term the phenomenon as "boss ceiling effect, " and term the behavior that people often downgrade their original choice to make sure the brand prestige is lower than that of the product owned by their boss as "downgrading behavior, " which have not been explored and well explained by existing literature so far. The paper aims to discuss this issue. Design/methodology/approach: The authors conduct qualitative study to explore the existence of boss ceiling effect and providing possible influential factors of brand downgrading attitude. The quantitative study empirically examines the relationships among undesired self, perceived risk, organizational culture balance, and downgrading attitude and intension. Findings: The authors find that undesired self-congruence and perceived risk are positively related to the downgrading attitude. In addition, the culture balance directly affects the brand downgrading attitude negatively and also moderates the relationship between undesired self-congruence and downgrading attitude positively and the relationship between perceived risk and downgrading attitude negatively. Originality/value: The authors contribute to both organizational culture research and symbolic consumption research by considering symbolic consumption behavior in organization context. It is of great practical implications for marketers of symbolic consumption to understand the downgrading behavior.